MESOAMERICAN FLAT CURVED STICKS: INNOVATIVE "TOLTEC" SHORT SWORD, FENDING STICK, OR OTHER PURPOSE?. Issue 1 (31st August 2017) - Geib, Phil R.
Abstract: Flat and curved sticks with longitudinal facial grooves were dredged from the Sacred Cenote at Chichen Itza in the early 1900s. They are similar to specimens recovered from the North American Southwest, where a suggested function was for defense against atlatl darts. By accepting this interpretation, Mesoamerican archaeologists identified such artifacts as fending sticks. Hassig (1992:112–114, 126–127, 2001:810–811) disputes this role, arguing that the sticks were specialized short swords for close fighting. This sword interpretation is not supported by my analysis of the Chichen Itza artifacts or the mural evidence at that site. Defense against atlatl darts is possible but unlikely to have occurred in warfare and, in any case, Maya/Toltec warriors carried shields to protect themselves against darts and other weapons. Fending darts in ritual fights such as an atlatl duel is a plausible scenario, perhaps to prove warrior mettle or as a gladiatorial blood sport. Another possible use is for subduing captives after military victory: a throwing stick to disable humans for later sacrifice.